Factors Associated with the Incidence of Gastritis in Adolescents at SMP Muhammadiyah 2 Kebumen: Faktor yang Berhubungan dengan Kejadian Gastritis pada Remaja di SMP Muhammadiyah 2 Kebumen - Rosyidi, Ahmad Anwar; Utami, Wuri (Prosiding University Research Colloquium, 2023)
Gastritis is one of the digestive disorders that often occurs both acutely and chronically, with 274,396 cases in Indonesia. Gastritis occurs due to a bad lifestyle, such as poor diet, stress that is not managed properly, and also bad coffee consumption. The purpose of this study was to analyze factors associated with the incidence of gastritis in adolescents at SMP Muhammadiyah 2 Kebumen. This study used quantitative methods of descriptive design of relationships (correlation) with Cross Sectional approach and random sampling techniques. The respondents used were 78 people. The instruments used are questionnaires and data are processed analysis using the chi-square test. The results of the study found that there was a relationship between diet and the incidence of gastritis (p: 0.000). There was no association between stress levels and gastritis incidence (p: 0.394), There was no association between coffee consumption and gastritis incidence (p: 0.264). Gastritis in adolescents results from various factors such as diet. Stress levels, and coffee consumption. The most influential factor on the incidence of gastritis in SMP Muhammadiyah 2 Kebumen is diet. This study is a correlation study without intervening with a sample of 78 respondents, it is hoped that future research will be able to examine.